REVIEW ON THE APPLICATION OF OPEN BANKING IN SHARIA BANKING: AN SWOT ANALYSIS - Egha Ezar Junaeka Putra Hassany; Galuh Tri Pambekti (LPPM, 2022)
This study was conducted to analyze SWOT (Strength, Weakness Opportunity, and Threat) Open Banking in Islamic banking in Indonesia. The analytical method used is descriptive literature research, namely by providing a description or description of the problems that have been identified and carried out intensively and in detail on a problem from the available literature. The results of this study indicate that there are several strategies that can be taken by Islamic Banking in dealing with Open Banking, including the S-O strategy: cooperation with fintech and e-commerce; and expand the network of cooperation nationally and internationally; W-O strategy: socializing open banking, improving technology and security, and increasing service complaints; S-T strategy: cooperate with other financial institutions, implement standardization prepared by the regulator; and W-O Strategy: multiple security enhancements, sorting out cooperation to third parties, and upgrading Islamic banking internal servers.